Multilateral commercial diplomacy - Curzon, Gerard. [from old catalog] (London : Michael Joseph Ltd, 1965)
This study is in no way a record of all Gatt has done or is trying to do. It is only an attempt to show how Gatt deals with some of the major contemporary commercial policies.
Includes bibliographical references, index
osc 24/07/2018
Loans
Keywords: International Economics